2017
DOI: 10.5897/ajar2017.12481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant density on the performance of selected African upland rice varieties

Abstract: The effects of plant density on yield and yield components in upland rice cultivation were examined by conducting a series of field experiments in Central Uganda, using three African and one Japanese improved upland rice varieties. The estimation of plant-density response functions with respect to yield components and yield revealed that an increase in plant density significantly decreased the number of panicles per hill, number of spikelets per panicle, and 1000-grain weight, and significantly increased the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
3
1
0
Order By: Relevance
“…There was no significant difference in the weight of 1000 seeds and the percentage of full seeds for both varieties for all spacing, whereas the differences were highly significant for the number of tillers per m 2 and significant for the number of grains per panicle. These results agree with those of Shunsuke, et al [7] who found that the weight of 1000 grains was not significantly different for different spacing. Other authors such as Clerget, et al [14], Hayashi, et al [15] and Nakano, et al [16] did not find similar results on the effect of plant density on the yield components.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…There was no significant difference in the weight of 1000 seeds and the percentage of full seeds for both varieties for all spacing, whereas the differences were highly significant for the number of tillers per m 2 and significant for the number of grains per panicle. These results agree with those of Shunsuke, et al [7] who found that the weight of 1000 grains was not significantly different for different spacing. Other authors such as Clerget, et al [14], Hayashi, et al [15] and Nakano, et al [16] did not find similar results on the effect of plant density on the yield components.…”
Section: Discussionsupporting
confidence: 93%
“…The results reveal that there was no significant difference for weight of 1000 grains for the two genotypes and across the years. These results match with those of Shunsuke, et al [7].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations